Identification of a neuron-specific ferroptosis in the neurodegenerative mucopolysaccharidosis III model - Larribau, Mathilde; Rouahi, Myriam; Santiago, Christophe; Ausseil, Jérôme; Karim, Zoubida (Frontiers in Molecular Biosciences, 2025)
Sanfilippo syndrome (MPSIII) is a neurodegenerative disorder caused by enzyme deficiencies, leading to the toxic accumulation of heparan sulfate oligosaccharides in the brain. Emerging evidence suggests that ferroptosis, an iron-dependent form of cell death, contribute to neurodegeneration. To investigate ferroptosis in MPSIIIB, we examined its regulatory mechanisms and markers in MPSIIIB brains. Our results showed elevated iron levels, decreased mRNA expression of TFR1 and ZIP14 (involved in iron uptake) at 9 months of age, and increased protein levels of FTH (which stores intracellular iron) in MPSIIIB brains, indicating a potential link to ferroptosis. We also observed diminished levels of ferroptosis-neutralizing proteins (xc-/GPX4), while the protective pathway (Keap1-Nrf2) was activated. Oxidative homeostasis disruption was revealed by increased expression of genes encoding SOD2, SIRT3, iNOS, and nNOS enzymes. Increased expression of lipid peroxidation genes (ascl4 and lpcat3) further supported ferroptosis involvement. Furthermore, we analyzed protein abundance and brain immunostaining of the iron exporter FPN. Despite its high expression levels, this protein appeared misfolded and was insufficiently targeted to cellular plasma membrane, which might contribute to cellular iron retention. The co-localization of FPN with NeuN, a marker of neurons, demonstrates that only neurons are affected by this targeting defect, suggesting neuronal ferroptosis specifically in MPSIIIB. Overall, our findings evidenced of the involvement of ferroptosis in MPSIIIB pathogenesis, highlighting dysregulation in iron homeostasis, antioxidant defenses, and lipid peroxidation as key features of the disease.